Biomimetic Non-Heme Iron-Catalyzed Epoxidation of Challenging Terminal Alkenes Using Aqueous H2O2 as an Environmentally Friendly Oxidant - Fingerhut, Anja; Vargas-Caporali, Jorge; Antonio Leyva-Ramirez, Marco; Juaristi, Eusebio; Tsogoeva, Svetlana (Molecules, 2019)
Catalysis mediated by iron complexes is emerging as an eco-friendly and inexpensive option in comparison to traditional metal catalysis. The epoxidation of alkenes constitutes an attractive application of iron(III) catalysis, in which terminal olefins are challenging substrates. Herein, we describe our study on the design of biomimetic non-heme ligands for the in situ generation of iron(III) complexes and their evaluation as potential catalysts in epoxidation of terminal olefins. Since it is well-known that active sites of oxidases might involve imidazole fragment of histidine, various simple imidazole derivatives (seven compounds) were initially evaluated in order to find the best reaction conditions and to develop, subsequently, more elaborated amino acid-derived peptide-like chiral ligands (10 derivatives) for enantioselective epoxidations.
CRIS-Team WoS Importer:2019-10-18

Non-heme iron catalysts for epoxidation and aziridination reactions of challenging terminal alkenes: towards sustainability - Tsogoeva, Svetlana; Fingerhut, Anja; Serdyuk, Olga (Green Chemistry, 2015)
Through catalytic epoxidation and aziridination of olefins versatile synthetic intermediates and subunits of biologically active compounds and pharmaceuticals -epoxides and aziridines-can be obtained. The focus of this review is on recent advances in the epoxidation and aziridination of challenging terminal alkenes with respect to safety of solvents or reagents used and atom economy aspects, as well as scope and limitations of developed non-heme iron catalysts. The still large research potential for sustainable and environmentally attractive iron-based catalysts in enantioselective epoxide and aziridine synthesis is demonstrated.

Synthesis and Electrochemical and Photophysical Characterization of New 4,4-Conjugated 2,2-Bipyridines that are End-Capped with Cyanoacrylic Acid/Ester Groups - Fingerhut, Anja; Wu, Yanlin; Kahnt, Axel; Bachmann, Julien; Tsogoeva, Svetlana (Chemistry-An Asian Journal, 2016)
Two new functionalized 4,4-disubstituted 2,2-bipyridines that were end-capped with cyanoacrylic acid or cyanoacrylic acid ester anchoring groups, which might allow their efficient functionalization on TiO2 or other metal-oxide semiconductor surfaces, have been synthesized and characterized by electrochemical, photophysical, and spectroscopic measurements. The electrochemical and photophysical properties of these 4,4-disubstituted 2,2-bipyridines with extended systems, in particular their LUMO energies, make them promising candidates to build up inorganic-organic hybrid photosensitizers for the sensitization of metal-oxide semiconductors (e.g., TiO2 nanoparticles and/or nanotubes).
Keywords: adsorption; bipyridines; conjugation; fluorescence; photosensitizers